HUBUNGAN POLA ASUH ORANG TUA DENGAN MOTIVASI MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI PADA REMAJA DI DAERAH PESISIR RIAU - Dewi, Yulia Irvani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Parenting style are very influential in behavior of adolescents. The aim of this research was to identify the correlation between parenting style and adolescents motivation to continue their education to collage in the Riau coastal areas. The design was descriptive correlational method with cross sectional approach. This research used purposive sampling technique involving 119 adolescents that was selected based on inclusion and exclusion criteria. This research used questionnaire for parenting style and motivation. The univariate analysis was conducted to determine the frequency distribution and the result showed that from 31 respondents with high motivation with the authoritative parenting style (79.5%), Respondent who with low motivation were 23 with the uninvolved parenting style (95.8%). Bivariate analysis was conducted by using chi-square test and the statistic showed p value (0.000) < alpha (0.05), which means that there is a correlation between parenting style and adolescents motivation to continue their education to collage in Riau coastal areas. Suggestion for parents to use authoritative parenting style for adolescents so their have motivation to continue education and self development. Keywords: Adolescents, Motivation, Parenting style